Coping with food and nutrition insecurity in Zimbabwe: Does household head gender matter? - Terrence Kairiza; George D. Kembo (Agricultural and Food Economics, 2019)
On the basis of a large-scale nationally representative sample of household data from five pooled cross-section surveys conducted by the Zimbabwe Vulnerability Assessment Committee (ZimVAC), this study assesses the existence of gender differences in the vulnerability to food and nutrition insecurity, usage of consumption-based and livelihoods-based coping strategies, and the existence of gender heterogeneity in the correlation of usage of such coping strategies when confronted by food and nutrition insecurity. The study offers three main findings. Firstly, female-headed households are more susceptible to food and nutrition insecurity than those headed by males. Secondly, female-headed households are more likely to employ consumption-based coping strategies than their male counterparts, but there is no statistically significant difference in the usage of livelihoods-based coping strategies. Finally, whilst there is little evidence of gender heterogeneity in the correlation of the usage consumption-based coping strategies, there is overwhelming evidence that female-headed household heads are less likely to adopt livelihoods-based coping strategies when confronted with food and nutrition insecurity. The sum total of these findings is that whilst female-headed households are more prone to food insecurity than their male counterparts, they are less able to use livelihoods-based coping strategies to weather household food and nutrition insecurity than their male counterparts.
Keywords: J16; Q18; 330; Gender differences; Food security